Community integration and its predictors in people with stroke: a multicenter longitudinal study - Jiang-Li Zhao; Lian-Dong Ma; Xiang Xiao; Li-Jun Lin; Hao Xie; Shamay S.M. Ng; Pei-Ming Chen (Medical Journals Sweden, 2024)
Objective: To investigate the community integration of patients following stroke and determine the predictors of their level of community integration at 1-year follow-up. Design: A multicenter, longitudinal, and observational study. Subjects: Sixty-five inpatients (41 men) with a mean age of 56.9 (standard deviation = 17.0) years, who had their first stroke at least 1 month prior to this study were recruited from 4 rehabilitation inpatient wards in China. Methods: In the initial assessment, the participants were evaluated using the Community Integration Questionnaire, the Fugl-Meyer Assessment, the Berg Balance Scale, the Modified Barthel Index, the Mini Mental State Examination, and the Modified Ashworth Scale. In the follow-up assessments, which were conducted via telephone no less than 1 year after discharge, the participants were evaluated using the Community Integration Questionnaire and also assessed for other disease-related conditions. Results: The participants' scores on the Community Integration Questionnaire in the follow-up assessment were significantly greater than those at the initial assessment (p < 0.05). In addition, the participants' Community Integration Questionnaire scores in the follow-up assessment were significantly correlated with their ages, numbers of years of education, and Modified Barthel Index, Berg Balance Scale, Mini Mental State Examination scores in the initial assessment (p < 0.05), and marginally significantly correlated with their scores on Fugl-Meyer Assessment in the initial assessment (p = 0.058). The participants' ages, numbers of years of education, and Modified Barthel Index, Berg Balance Scale, Mini Mental State Examination, Fugl-Meyer Assessment of the lower extremity, and Fugl-Meyer Assessment scores in the initial assessment were predictive of their Community Integration Questionnaire scores at follow-up, with coefficients of determination ranging from 0.254 to 0.056 (p < 0.05). Conclusions: The level of community integration of the participants was generally low, but it was greater at 1-year follow-up than it was initially. Balance function and daily living ability may be key predictors of community integration of patients following stroke.